New species of the scale worm genus Pholoe (Polychaeta: Pholoidae) from southeast Brazil - Padovanni, Nathalia; Amaral, Antonia Cecília Z. (Zootaxa, 2013)
Exploration of poorly known regions of the Brazilian coast has resulted in the discovery of a new species in the scale worm family Pholoidae. Pholoe microantennata sp. nov. occurs at the Campos Basin (states of Espírito Santo and Rio de Janeiro) and along the northern coast of São Paulo State. It differs from other species in the genus because it has numerous large and conical marginal papillae on the elytra and two small lateral antenna attached to the distal portion of the prostomium. The family Pholoidae remains species-poor compared with most polychaete families, and it currently comprises 24 species worldwide. In Brazil, only three species of this family have been recorded.